Enhancing competitiveness by education and training - Svetličič, Marjan (Mednarodno inovativno poslovanje, 2010)
In today's quickly changing social and economic environment and the growing trend towards globalisation, there has to be a new way of looking at the ways to improve productivity and growth in the EU and Slovenia. One method that can create this change is by reviewing and updating education practices. With updated education practices, we can improve upon the creativeness and innovativeness that will lead us forward in the upcoming decades. The influence of education on society and business is immense. Countries with higher education standards tend to have higher wealth per person than those countries where education is lacking. However, just having a higher education standard is not enough. There has to be a focus on the quality of education as well, since in most cases the type of education receive determines the quality of the work force and socio-economic standing. In the modern globalised world economy, it is not enough to offer students lesson programmes where their only objective is to memorise data and facts. There must be a shift in teaching practices where teachers are give more opportunities and the autonomy to teach students about thinking creatively and developing their "soft skills", such as cultural awareness, critical and creative thinking and communication competencies. These skills along with the basics of education will help create life-long learners who will be ready to be competitive in the rapidly expanding global market. Many companies are aware of these "soft skills" and are actively seeking out potential employees who possess these skills. There must be an effort to train and inspire teachers on these new ideologies who will then be able to turn around and pass their knowledge and new ways of learning to the upcoming generations. Education must be made a priority. Competition in the globalised market is only going to get tougher and by re-evaluating learning programmes and adding new methods, students can leave their formal education with the curiosity and desire for life-long learning that will give them the competitive edge in the market place, improving their chances for success as well as contributing to the success of Slovenia.
Keywords: Competitiveness; Economy; Education; Gospodarstvo; Izobraževanje; Konkurenčnost